TAMI-05. THE IRRADIATED BRAIN MICROENVIRONMENT SUPPORTS GLIOMA STEMNESS AND SURVIVAL VIA ASTROCYTE-DERIVED TRANSGLUTAMINASE 2. (9th November 2020) - Berg, Tracy; Marques, Carolina; Pantazopoulou, Vasiliki; Johansson, Elinn; von Stedingk, Kristoffer; Lindgren, David; Pietras, Elin; Bergström, Tobias; Swartling, Fredrik; Governa, Valeria; Bengzon, Johan; Belting, Mattias; et al.
Abstract: The highest-grade gliomas invariably recur as incurable tumors following standard of care comprising surgery, radiotherapy, and chemotherapy. The majority of the recurrent tumors form within the area of the brain receiving high-dose irradiation during treatment of the primary tumor, indicating that the recurrent tumor forms in an irradiated microenvironment. The tumor microenvironment has been demonstrated to influence the therapeutic response and stemness characteristics of tumor cells, but the influence of radiation on the microenvironment and its subsequent consequences for tumor cells are incompletely understood. Here, we used genetically engineered glioma mouse models and human glioma samples to characterize the impact of standard of care radiotherapy on the brain tumor microenvironment. We found that tumor-associated astrocytes subjected to radiation in vitro could enhance tumor cell stemness and survival of co-cultured glioma cells. More aggressive gliomas formed in vivo when mouse brains were irradiated prior to tumor cell implantation, suggesting that the irradiated brain microenvironment supports tumor growth. We isolated the effect of irradiated astrocytes to extracellular matrix secreted by these cells, and specifically found that astrocyte-derived transglutaminase 2 (TGM2) is a stromal promoter of glioma stemness and radioresistance. TGM2 levels were increased after radiation in glioma mouse models. Recombinant TGM2 enhanced, and TGM2 inhibitors blocked, glioma cell stemness. In human GBM tissue, TGM2 levels were increased in recurrent vs. primary tumors. In summary, in addition to supporting TGM2 as a potential therapeutic target in glioma, our data indicate that radiotherapy results in a tumor-supportive microenvironment, the targeting of which may be necessary to overcome tumor cell therapeutic resistance and recurrence.